2016
DOI: 10.1097/igc.0000000000000809
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthermic Intraperitoneal Perfusion Chemotherapy and Cytoreductive Surgery for Controlling Malignant Ascites From Ovarian Cancer

Abstract: Hyperthermic intraperitoneal chemotherapy is effective at controlling ascites in patients with OC, even for patients in poor condition before CRS, or when complete CRS is not feasible. Furthermore, the regression of ascites appears not to be dependent on complete resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Rates of complete cytoreduction (R0 resection) varied from 50% to 100% in these trials, [38][39][40][42][43][44][45][46][47][48]50,51 and univariable and multivariable analyses showed that residual disease after debulking was the strongest predictor of OS. 38,39,[43][44][45]53,55 Therefore, NCCN recommends maximum effort to achieve complete cytoreduction during IDS, regardless of whether HIPEC is planned.…”
Section: Hyperthermic Intraperitoneal Chemotherapy At the Time Of Idsmentioning
confidence: 99%
“…Rates of complete cytoreduction (R0 resection) varied from 50% to 100% in these trials, [38][39][40][42][43][44][45][46][47][48]50,51 and univariable and multivariable analyses showed that residual disease after debulking was the strongest predictor of OS. 38,39,[43][44][45]53,55 Therefore, NCCN recommends maximum effort to achieve complete cytoreduction during IDS, regardless of whether HIPEC is planned.…”
Section: Hyperthermic Intraperitoneal Chemotherapy At the Time Of Idsmentioning
confidence: 99%
“…This recommendation is based on the evidence that the synergistic effect of hyperthermia and cisplatin can be dramatically increased at 42°C [10]. Data from clinical research also confirmed the safety and effectiveness of HIPEC at 43°C [31][32][33][34]. In general, the properties of biological tissues, the toxicity of drugs and their mutual influences change under hyperthermic conditions; some of the changes are temperature dependent [35].…”
Section: Hipec-related Aes Are Summarized In Supplementarymentioning
confidence: 99%
“…Alternatively, Ba et al placed catheters laparoscopically and then performed the first session of HIPEC in the operating room followed by two more sessions in the ICU on postoperative days 1 and 2. Both Ba and Valle found an average increase in Karnofsky performance scores (KPS) of 20 points after treatment. Orgiano et al found an increase in median PuFS from 11.2 to 39.5 days .…”
Section: Treatmentmentioning
confidence: 99%
“…Orgiano et al found an increase in median PuFS from 11.2 to 39.5 days . Adverse effects associated with HIPEC include nausea, vomiting, abdominal pain, abdominal wall metastases, peritoneal inflammation, neutropenia, and bone marrow suppression …”
Section: Treatmentmentioning
confidence: 99%